“Constant Enemies of the Christian Name”: Tracing the Construction of the Ritual Murder Charge in The Life and Miracles of St. William of Norwich - Joffe, Rose (Iggrot Ha’Ari, 2025)
This paper examines the construction of the blood libel myth in Thomas of Monmouth’s 12th-century manuscript, The Life and Miracles of St. William of Norwich. Building upon existing scholarship, it analyzes Life as both a martyrdom narrative and an anti-Jewish polemic. Drawing on Elizabeth Castelli’s theory of martyrdom and collective memory, this paper argues that the rhetorical construction of the Jew as a biblical, bloodthirsty enemy of Christ served to reinforce a dubious martyrdom narrative and consolidate a medieval Christian identity perceived as under threat. By deconstructing the rhetorical devices underpinning the account’s blood libel charge–literary foil, biblical metaphor, and the Christ-killer accusation– the paper highlights how Monmouth successfully transformed Jews from victims of conspiracy to perpetrators of violent crime. Monmouth’s use of a literary foil drew on prevailing ideas of Christian-Jewish difference to reinforce notions of Christian piety, while his invocations of biblical metaphor stabilized a tenuous assertion of Jewish guilt and Christian persecution. These anti-Jewish rhetorics culminate in Monmouth’s invocation of the Christ-killer myth. By likening medieval Jews to the biblical betrayers of Christ, Monmouth created a universal framework that rationalized and justified the violent persecution of Jews.